Exploring the impact of vertically separated flows on wind loads of multi-level structures - Mohammadjani, Chia; Zisis, Ioannis (Frontiers in Physics, 2023)
The complex dynamics of vertically separated flows pose a significant challenge when it comes to assessing the wind loads on multi-level structures, demanding a nuanced understanding of the intricate interplay between atmospheric conditions and architectural design. Previous studies and wind loading standards provide insufficient guidance for designing wind pressures on multi-level buildings. The behavior of wind around perpendicularly attached surfaces is not quite similar to that of individual flat roofs or walls. When a body is comprised of several surfaces with right or oblique angles, the separated flow from surfaces and their interactions will cause complex flow patterns around each surface. A wind tunnel experimental study was carried out on bluff bodies with attached flat plates and other adjacent bluff bodies with different heights to examine the wind-induced pressures on such complex shapes. Mean and peak pressure coefficients were measured to determine the flow interaction patterns and location of localized peak pressures. The results were compared to the Tokyo Polytechnic University (TPU) Aerodynamic Database of isolated low-rise buildings without eaves. The research findings indicated that there was a noteworthy disparity between the minimum and maximum values and locations of peak pressures on both the wall and roof surfaces of the models used in this study, as compared to the results obtained by the TPU. Moreover, the study conceivably pointed to difference in between the peak negative and positive pressure coefficient locations with the ASCE 7-22 wind loading zones. The peak suction zones were affected by the combined flows at perpendicular faces and as a result different wind load zones were obtained dissimilar to those introduced by the ASCE 7-22. Wind loading standards may need to be modified to account for the wind pressures on complex building structures with an emphasis on the location of the peak negative pressure zones.